BUILDING AND COMMUNICATING BRAND BY MICRO, SMALL AND MEDIUM ENTERPRISES (MSMEs) - Yocky Pramudya Ananda (Universitas Pasundan, 2022)
The role of Micro, Small and Medium Enterprises (MSMEs) in the national economy is quite large. The number reached 99.9 percent and employment absorbed 97 percent. At present, SMEs contribute 60.34 percent of GDP. Business strategies in building business sustainability that develops and differ from time to time require MSMEs to always improve the quality of products or services through continuous improvement so as to encourage increased market share and win the competition. The ability of MSMEs to access and manage various resources is still considered difficult. This view shows the weak foundations of MSMEs in terms of capital and marketing which become obstacles in the face of competition. In the effort to build a UMKM Relativity Business, it is the ability of UMKM to face challenges, obstacles, weaknesses, and limitations that have become strengths and opportunities to compete. The dynamism of the competitive advantage of MSMEs that changes rapidly in meeting demand, the existence of competing products, the application of technology, and the consistency of policies that support MSMEs are factors that influence the survival of MSMEs to dynamically change the buying interest of MSME consumers. Failure to communicate brands by MSMEs because of the power of digitalization maximized by SMEs. The factors causing the failure of UMKM were due to the lack of knowledge, ability and awareness of UMKM to follow the development of digitalization